Efficacy of a Laparoscopic Saline-Coupled Bipolar Sealer in Minimally Invasive Hepatobiliary Surgery. (December 2019) - Sastry, Amit; Sulzer, Jesse K.; Passeri, Michael; Baker, Erin H.; Vrochides, Dionisios; McKillop, Iain H.; Iannitti, David A.; Martinie, John B.
Hepatic resection presents unique surgical challenges to reduce blood loss during parenchymal division. The development of saline-coupled bipolar devices, in which hemostasis is achieved at lower temperatures than electrocautery or other bipolar sealing devices, have been employed for open hepatic resection. Saline-coupled bipolar devices have now become available for minimally invasive use. The goals of this study were to evaluate the feasibility and safety of a laparoscopic saline-coupled bipolar device for minimally invasive hepatectomy. Seventeen patients (median age 66 years, range 36-81) were consented for inclusion and enrolled. Patient demographics, intraoperative data, and surgeon feedback were collected. Seven robot-assisted partial hepatectomies, 9 laparoscopic partial hepatectomies, and 1 laparoscopic cholecystectomy with liver abscess resection were performed. Average operating time was 222 ± 33 minutes (median 188 minutes; range 61-564 minutes) with no difference between robotic versus laparoscopic time. Successful seals were achieved in all cases following application of 150 to 200 J energy (average 179 ± 3 J, average time to achieve a successful seal 9.3 ± 2.7 minutes). Estimated blood loss was 362 ± 74 mL (median 300 mL, range 5-1200 mL) and 3/17 patients received intraoperative blood transfusion. No bile leaks were detected in any of the patients. Median length of stay was 5 days (range 1-20 days), and there were no readmissions within 30 days. Postoperative morbidity occurred in 5/17 patients, all of which were Clavien Grade 1. There was no mortality within 90 days or complications requiring a return to the operating room, and there were no liver-specific morbidities. These data suggest the laparoscopic Aquamantys device represents a useful device for use in minimally invasive liver resection.